Five new species of Stauroneis (Bacillariophyta, Stauroneidaceae) from the northern Rocky Mountains, USA - Bahls, Loren (Phytotaxa, 2012)
Five new species of Stauroneis are described from the northern Rocky Mountains—S. clarkii, S. lewisii, S. sacajaweae, S. spauldingiae, and S. thompsonii—for a total of 21 new Stauroneis species from the region. All of the new species are local or regional endemics. Water bodies supporting populations of Stauroneis tend to be small, remote, isolated, circumneutral, oligo- or dystrophic, and with low levels of electrolytes. These findings have implications for estimating diatom biodiversity and for conserving endemic diatom species and their habitats.